Types Of Practical Graphics And Its Place In The System Of Continuous Education - Rajabova Laylo O‘tkir qizi (Genius Journals, 2024)
In computer graphics, computers are used as a means of creating images, as well as for processing visual data obtained in one way or another and stored on a computer. Types of applied graphics and its place in the continuing education system, including the purpose and tasks of applied graphics.
Keywords: Computer graphics; creativity; graphic program